2017
DOI: 10.1183/13993003.02538-2016
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a-5p plays an essential role in the aberrant epithelial–fibroblast cross-talk in COPD

Abstract: We previously reported that epithelial-derived interleukin (IL)-1α drives fibroblast-derived inflammation in the lung epithelial-mesenchymal trophic unit. Since miR-146a-5p has been shown to negatively regulate IL-1 signalling, we investigated the role of miR-146a-5p in the regulation of IL-1α-driven inflammation in chronic obstructive pulmonary disease (COPD).Human bronchial epithelial (16HBE14o-) cells were co-cultured with control and COPD-derived primary human lung fibroblasts (PHLFs), and miR-146a-5p expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 34 publications
2
49
1
1
Order By: Relevance
“…This common G>C SNP in pre-miR-146a-5p has been associated with decreased expression of the mature miR-146a-5p [11]. Unexpectedly, in the present study, a lower miR-146a-5p expression was observed in fibroblasts from donors homozygous for the G allele of SNP rs2910164, which were all but one COPD patient [5]. A validation study in a large independent cohort will be needed to verify these results.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…This common G>C SNP in pre-miR-146a-5p has been associated with decreased expression of the mature miR-146a-5p [11]. Unexpectedly, in the present study, a lower miR-146a-5p expression was observed in fibroblasts from donors homozygous for the G allele of SNP rs2910164, which were all but one COPD patient [5]. A validation study in a large independent cohort will be needed to verify these results.…”
supporting
confidence: 50%
“…Importantly, this increase of miR-146a-5p was impaired in fibroblasts from patients with COPD, which releases the brake on the IL-1R/NF-κB pathway and is likely to contribute to the abnormal inflammation in COPD. Interestingly, treating fibroblasts with an miR-146a-5p mimic downregulated the expression of IRAK-1, resulting in a reduced release of IL-8 and confirming the anti-inflammatory role of miR-146a-5p [5]. It is worth noting that the inability of COPD fibroblasts to upregulate miR-146a-5p not only leads to an impaired negative feedback regulation of NF-κB signalling, but also results in a reduced mRNA degradation and thus prolonged half-life of cyclooxygenase (COX)-2, another target of miR-146a-5p [10].…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Notably, miR-146a-5p was previously reported to be involved in airway inflammation associated with smoking and COPD [10] and to inhibit MUC5AC production in vitro [21]. We recently found miR-146a-5p to be higher expressed in non-COPD lung fibroblasts upon co-culture with bronchial epithelial cells, while there was significantly less increase in COPD fibroblasts, suggesting a role for miR-146a-5p in disturbed epithelial-fibroblast crosstalk in COPD [22]. Our present findings suggest that miR-146a-5p may also be involved in mucus hypersecretion via epithelial-fibroblast crosstalk; however, it is not yet clear via which target gene nor in which cell type it has its main effect on CMH.…”
Section: Discussionmentioning
confidence: 85%